2019
DOI: 10.3390/polym11020312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Spray Drying Conditions of Blueberry Juice-Maltodextrin on the Yield, Content, and Retention of Quercetin 3-d-Galactoside

Abstract: The influence of the processing conditions during the spray drying of mixtures of blueberry juice (BJ) and maltodextrin (MX) was determined quantitatively by the analysis of variance (ANOVA), and qualitatively by the surface response plots (SRP). The effect of two independent variables (inlet temperature, and MX concentration), and one categorical variable (type of MX), was determined on the yield (Y), content (Q), and retention (R) of the antioxidant quercetin 3-d-galactoside. From the ANOVA results, the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Saavedra-Leos et al determined an inverse relation between T g and DE of maltodextrins [21]. Through several works reported by the Saavedra-Leos group [14,22,37,38,39], we have observed that in some juices such as orange and blueberries, their physicochemical properties varied with the differences in the type and distribution of molecular weight of the carrier agent. In these studies, we have attributed this behavior mainly to: (i) Differences in the molecular weight distribution of the carrier agent, (ii) the arrangement of polymer chains (i.e., entangled or linear) and (iii) the type of molecule in these chains (for example, glucose for maltodextrin or fructose for inulin).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Saavedra-Leos et al determined an inverse relation between T g and DE of maltodextrins [21]. Through several works reported by the Saavedra-Leos group [14,22,37,38,39], we have observed that in some juices such as orange and blueberries, their physicochemical properties varied with the differences in the type and distribution of molecular weight of the carrier agent. In these studies, we have attributed this behavior mainly to: (i) Differences in the molecular weight distribution of the carrier agent, (ii) the arrangement of polymer chains (i.e., entangled or linear) and (iii) the type of molecule in these chains (for example, glucose for maltodextrin or fructose for inulin).…”
Section: Resultsmentioning
confidence: 73%
“…In this section we compared the results of the content of resveratrol reported herein, against those for quercetin 3-D-galacoside previously reported [22]. The effect of spray drying processing conditions showed similar behavior for both antioxidants, but the main difference relied on the values of the content of each antioxidant.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations